Diabetes mellitus 1. typu a sdruzená autoimunitní onemocnĕní u prvostupnových príbuzných diabetických dĕti: výsledky dotazníkové studie - Malcová, H; Sumník, Z; Drevínek, P; Lebl, J; Venhácová, J; Vavrinec, J; Cinek, O (Casopis lekaru ceskych, 2004)
BACKGROUND: Type 1 diabetes mellitus (T1DM) is associated with increased incidence of other autoimmune diseases. The shared genetic background may play a role in the disease pathogenesis. The aim of our study was to assess the prevalence of T1DM and other autoimmune disorders in the first-degree relatives of diabetic children. METHODS AND RESULTS: Data were retrospectively obtained using structured questionnaires from 868 diabetic children younger than 18 years (434 girls and 434 boys, age 12.5 +/- 4.0, mean +/- SD) and their 2704 relatives. The control group included 1466 non-diabetic schoolmates and friends (796 girls, 670 boys, age 11.9 +/- 4.5) and their 4510 first-degree relatives. In the questionnaire we asked about occurrence of thyroid and celiac disease in cases and controls, and about occurrence of T1DM, thyroid and celiac disease in their first-degree relatives. We observed significantly higher prevalence of T1DM in fathers (4.4% vs. 0.8%), mothers (2.0% vs. 0.5%) and siblings (2.5% vs. 0%) of diabetic children compared to controls. Thyroid disease was found significantly more in diabetic children (10.0% vs. 1.9%) and their siblings (3.1% vs. 1.7%). Prevalence of celiac disease was also higher in diabetic children than in controls (3.2% vs. 0.5%), but it does not differ in their first-degree relatives. CONCLUSIONS: We found significantly higher prevalence of thyroid and celiac disease in T1DM children than in controls. Targeted screening and early detection of thyroid and celiac diseases in T1DM patients are likely to be necessary. We observed an increased prevalence of T1DM and thyroid disease in first-degree relatives of diabetic children, however screening of autoimmune diseases associated with T1DM in the first-degree relatives remain controversial.
Keywords: autoimunitní tyreoiditida; autoimunitní nemoci; Humans; dítě; Child; Female; rodiče; dospělí; Siblings; lidé; Parents; sourozenci; Autoimmune Diseases; diabetes mellitus 1. typu; Adult; Thyroiditis, Autoimmune; celiakie; ženské pohlaví; Male; Celiac Disease; mužské pohlaví; Diabetes Mellitus, Type 1